A case study of KELHELDEPT : the implications of medical officer doing administrative work - Mohamad Norazam Abdullah; Azwan Abdullah (Faculty of Entrepreneurship and Business,UMK, 2015)
This case study developed based on the reasons to investigate and to comprehend what are the implications arise when Medical Officer at KelHelDept doing administrative work as opposed to honing their medical skills to treat patients. This study tends to understand whether this action is threats or give good implications to them and organization. The finding of the study revealed that there are positive and negative implications of this exercise. The findings from this study describe what are the benefit emerge from this kind of policy and what are the implications could be face by medical officers and the organization itself and also what are the factors that drive this practices or action. Based on the findings, this study recommends several suggestions to improve the situation for sake of medical officer’s career path and also for the organization. The findings from this study are expected to help the Ministry of Health in designing and improving policies related to medical officer. A framework of regarding the placement of medical officer has been proposed to enhance the decision making process with hope it can serve better the organization dan finally the citizen. This case study uses qualitative approach to define the issues, collecting data and propose the suggestions. To complete this, five (5) informants from clinical background (medical officer) who doing administrative work were interviewed in order to gather the informations needed.